SEKILAS TENTANG MANAJEMEN BISNIS SYARIAH - Karsidi Karsidi (Faculty of Economics and Business Universitas Jenderal Soedirman, 2013)
Islam is a religion having complete and balance in its doctrine. Complete doctrine means that Islam provides a complete guidance for all affairs of life and the balance in Islam means that the religion does not only give a guidance to reach the hereafter happiness, but also gives a guidance how to reach the happiness in the world. In order to reach the happiness in the world, Islam orders and guides human beings to conduct efforts in any which way they can to fulfill their living allowance. The efforts are called “muamalah”. There are many kinds of “muamalah”, one of them is called Business. The business should be run based on the rules ordered and blessed by Alloh SWT. Such a business in known as the Syariah Business Management.